The effects of acute hypoxia on tissue oxygenation and circulating alarmins in healthy adults - Boos, C. J; Lamb, C. M; Midwinter, M; Mellor, A; Woods, D. R; Howley, M; Stansfield, T; Foster, M; O'Hara, J. P (Physiological research, 2018)
The binding of high-mobility group box-1 (HMGB-1) to the membrane receptor for advanced glycation end-products (mRAGE) is a key early mediator of non-infectious inflammation and its triggers include ischaemia/hypoxia. The effects of acute hypoxia on soluble RAGE (sRAGE) are unknown. Fourteen healthy adults (50 % women; 26.6+/-3.8 years) were assessed at baseline normoxia (T0), followed by four time-points (T90, 95, 100 and 180 min) over three hours of continuous normobaric hypoxia (NH, 4,450 m equivalent) and again 60 min after return to normoxia (T240). A 5-min exercise step test was performed during NH at T90. Plasma concentrations of HMGB-1, sRAGE VCAM-1, ICAM-1, VEGF IL-8 and IL-13 were measured using venous blood. Arterial and tissue oxygen saturations were measured using pulse oximetry (SpO(2)) and near-infrared spectroscopy (StO(2)), respectively. NH led to a significant reduction in SpO(2), StO(2), sRAGE and VEGF, which was compounded by exercise, before increasing to baseline values with normoxic restoration (T240). NH-exercise led to a paired increase in HMGB-1. sRAGE inversely correlated with HMGB-1 (r=-0.32; p=0.006), heart rate (r=-0.43; p=0.004) but was not linked to SpO(2) or StO(2). In conclusion, short-term NH leads to a fall in sRAGE and VEGF concentrations with a transient rise post NH-exercise in HMGB-1.
Keywords: dospělí; Inflammation Mediators; Prospective Studies; Humans; Alarmins; prospektivní studie; Hypoxia; alarminy; mladý dospělý; spotřeba kyslíku; Receptor for Advanced Glycation End Products; hypoxie; Vascular Endothelial Growth Factor A; mužské pohlaví; vaskulární endoteliální růstový faktor A; receptor pro konečné produkty pokročilé glykace; Adult; biologické markery; Oxygen Consumption; HMGB1 Protein; ženské pohlaví; mediátory zánětu; lidé; Biomarkers; Male; Young Adult; protein HMGB1; Female